Utilization of teacher's development towards lifelong learning: an innovative assessment - Mohamad Mustafa, Maslina; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
In ensuring the students to be provided with the 21st century skills, new form of innovative assessment has been introduced to replace the conventional assessment practice. Such assessment practice also now has been widely implemented. The focus is now on ensuring that the assessment process is in line with the other component of the curriculum. This is done to ensure that individual that can compete at the global level can be produced. Hence, a literature review has been conducted to identify the advantages of implementation of the innovative learning. This paper also discussess a few elements that need to be taken into consideration in ensuring the implementation of the assessment to run smoothly.